Trk-fused gene (TFG) regulates pancreatic β cell mass and insulin secretory activity. Issue 1 (December 2017) - Yamamotoya, Takeshi; Nakatsu, Yusuke; Kushiyama, Akifumi; Matsunaga, Yasuka; Ueda, Koji; Inoue, Yuki; Inoue, Masa-Ki; Sakoda, Hideyuki; Fujishiro, Midori; Ono, Hiraku; Kiyonari, Hiroshi; Ishihara, Hisamitsu; et al.
Abstract The Trk-fused gene (TFG) is reportedly involved in the process of COPII-mediated vesicle transport and missense mutations in TFG cause several neurodegenerative diseases including hereditary motor and sensory neuropathy with proximal dominant involvement (HMSN-P). The high coincidence ratio between HMSN-P and diabetes mellitus suggests TFG to have an important role(s) in glucose homeostasis. To examine this possibility, β-cell specific TFG knockout mice (βTFG KO) were generated. Interestingly, βTFG KO displayed marked glucose intolerance with reduced insulin secretion. Immunohistochemical analysis revealed smaller β-cell masses in βTFG KO than in controls, likely attributable to diminished β-cell proliferation. Consistently, β-cell expansion in response to a high-fat, high-sucrose (HFHS) diet was significantly impaired in βTFG KO. Furthermore, glucose-induced insulin secretion was also markedly impaired in islets isolated from βTFG KO. Electron microscopic observation revealed endoplasmic reticulum (ER) dilatation, suggestive of ER stress, and smaller insulin crystal diameters in β-cells of βTFG KO. Microarray gene expression analysis indicated downregulation of NF-E2 related factor 2 (Nrf2) and its downstream genes in TFG depleted islets. Collectively, TFG in pancreatic β-cells plays a vital role in maintaining both the mass and function of β-cells, and its dysfunction increases the tendency to develop glucose intolerance.